Q: M Squared minus M Squared and why?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

By factoring I get x-3 divided by x+3

xsquared minus x minus 72

9 minus 8

7x2 -4x -5x2 +2x = 2x2 -2x

Same as (A-B)x(A+B)

Related questions

m2 - 4mn - 12n2 = m2 - 6mn + 2mn - 12n2 = m(m - 6n) + 2n(m - 6n) = (m + 2n)(m - 6n)

2m^2 - 8 -First you should factor out a two. --> 2(m^2-4) -You now have something squared minus something else squared; You have m squared minus 2 squared. Whenever you have something squared minus something squared as you do in this case, there is a simple rule to remember: You can reduce that expression into the quantity of the square root of the first number or variable plus the square root of the second number or variable Times the quantity of the square root of the first number or variable minus the second number or variable squared. --> In the case of your expression: ----> 2(m+2)(m-2)<-----

3x squared minus 25x minus 28

2x squared minus 4

No, unless "a" happens to be equal to 0, or to 1.

-22 - -22

x = ? 42 = x squared minus x

hello

(x-12)2 using perfect square

3m^2 - 9m = 0 factor out 3m 3m(m - 3) = 0 m = 0 -------- or m = 3 --------

(9y+2z)(y-3z)

m = 9 This is because, if: m squared - 2m - 65 = 2 Then: m squared - 2m = 65 + -2 m squared - 2m = 63 So: 63 = m squared - 2m m squared - 2m = m x m - 2m This means: 63 = m (m - 2) So something times itself minus two is 63. Going through different numbers, it is clear that 9 and 7 work. So: m x (m - 2) = 9 x (9-2) = 9 x (7) = 9 x 7 = 63 M is therefore 9.